High‐Performance Thermomagnetic Generators Based on Heusler Alloy Films. Issue 5 (18th November 2016) - Gueltig, Marcel; Wendler, Frank; Ossmer, Hinnerk; Ohtsuka, Makoto; Miki, Hiroyuki; Takagi, Toshiyuki; Kohl, Manfred
Abstract : Recent developments on Heusler alloys including Ni–Mn–X and Ni–Co–Mn–X (X = Ga, In, Sn, …) demonstrate multiferroic phase transformations with large abrupt changes in lattice parameters of several percent and corresponding abrupt changes in ferromagnetic ordering near the transition temperatures. These materials enable a new generation of thermomagnetic generators that convert heat to electricity within a small temperature difference below 5 K. While thermodynamic calculations on this energy conversion method predict a power density normalized to material volume of up to 300 mW cm −3, experimental results have been in the range of µW cm −3 . Challenges are related to the development of materials with bulk‐like single‐crystal properties as well as geometries with large surface‐to‐volume ratio for rapid heat exchange. This study demonstrates efficient thermomagnetic generation via resonant actuation of freely movable thin‐film devices of the Heusler alloy Ni–Mn–Ga with unprecedented power density of 118 mW cm −3 that compares favorably with the best thermoelectric generators. Due to the large temperature‐dependent change of magnetization of the films, a periodic temperature change of only 3 K is required for operation. The duration of thermomagnetic duty cycle is only about 12 ms, which matches with the period of oscillatory motion. Abstract : Heusler alloy materials showing multiferroic phase transformations enable a new class of thermomagnetic generators. While thermodynamic calculations predict high power densities, experimental results have lacked behind. Now, an efficient thermomagnetic generation method is presented making use of resonant actuation of freely movable Heusler alloy film devices at small magnetic field within small temperature difference.